Energy Efficiency Clauses in Charter Party Agreements Legal and Economic Perspectives and their Application to Ocean Grain Transport - Psarros, George Adamantios; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides practical solutions for addressing energy efficiency as a clause term within a charter party contract. For this, upon a reflection of the regulatory craft, it analyzes key concepts of case law, and discusses them together with commercial and economic principles. In this way, the book aims at offering a comprehensive, interdisciplinary view of the chartering process, together with a new approach for safeguarding energy efficiency investments. A special emphasis is given to the maritime industry. Here, the newly developed framework, based on game theory, has been successfully applied to demonstrate the importance of including a clause term in contract negotiation to achieve protection against both an uncertain market and an even more challenging shipping environment. The book not only fills a gap in the literature, covering a topic that has been largely neglected to date, yet it offers researchers and practitioners extensive information to change the chartering processradically.
Introduction -- Qualitative Part -- Quantitative Part -- Epilogue.
Keywords: Industrial Management; Energy policy; Energy and state; International law; Trade regulation; Game theory; Industrial Management; Energy Policy, Economics and Management; International Economic Law, Trade Law; Game Theory